INTEGRATED SWITCH OPERATION MODE RECTENNA FOR RADIO AM - Fadhli Hilman Zhafari; Rudy Yuwono (Jurnal Mahasiswa TEUB, 2019)
Radio adalah teknologi yang digunakan untuk pengiriman sinyal dengan cara modulasi dan radiasi elektromagnetik (gelombang elektromagnetik). Radio juga merupakan perangkat elektronik yang digunakan sebagai media komunikasi dan informasi. Penggunaan radio pada dahulu banyak digunakan sementara pada sekarang penggunaannya sudah berkurang dikarenakan adanya internet. Walaupun, pemancar stasiun radio tetap memancarkan gelombang elektromagnetik. Hal ini dapat menyebabkan penggunaan gelombang elektromagnetik yang tidak efisien. Sehingga diperlukan adanya rectifier untuk menyerap gelombang elektromagnetik tersebut. Pada penelitian ini digunakan rectifier pada frekuensi AM. Pada penelitian ini terdapat dua buah alat yang digunakan untuk perbandingan hasilnya. Kedua alat itu yaitu Non- Integrated Switch Operation Mode Rectenna (Non-ISOMR) dan Integrated Switch Operation Mode Rectenna on Radio (ISOMRR). Pada Non-ISOMR terdapat empat buah kondisi pengujian yaitu rectenna on kapasitor on, rectenna on kapasitor off, rectenna off kapasitor on dan rectenna off kapasitor off. Pada ISOMRR terdapat empat buah kondisi percobaan juga yaitu, radio on rectifier on, radio on rectifier off, radio off rectifier on, dan radio off rectifier off. Dari tiap kondisi tersebut dilakukan pengujian tegangan, arus keluaran rectifier yang selanjutnya dikalikan yang menghasilkan daya keluaran rectifier. Kata kunci: radio, rectifier, rectenna, ISOMRR, Non-ISOMR ABSTRACT Radio is a technology used for signal transmission by modulation and electromagnetic radiation (electromagnetic waves). Radio is also an electronic device that is used as a medium of communication and information. The use of radio in the past was widely used while now its use has been reduced due to the internet. Although, the radio station transmitter still emits electromagnetic waves. This can lead to the use of inefficient electromagnetic waves. So we need a rectifier to absorb electromagnetic waves. In this study rectifiers used in AM frequencies. In this study there are two tools used for comparison of the results. Both devices are Non-Integrated Switch Operation Mode Rectenna (Non-ISOMR) and Integrated Switch Operation Mode Rectenna on Radio (ISOMRR). In Non-ISOMR there are four test conditions, namely rectenna on capacitor on, rectenna on switch off, rectenna off capacitor off and rectenna off capacitor off. At ISOMRR there were four experimental conditions, namely radio on rectifier on, radio on rectifier off, radio off rectifier on, and radio off rectifier off. From each of these conditions a voltage test is performed, the rectifier output current is multiplied which produces the rectifier output power. Keywords: radio, rectifier, rectenna, ISOMRR, Non-ISOMR